Sekularisasi: Refleksi terhadap Konsep Ketuhanan - Ahida, Ridha (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
Love to God and religion, in one side, has succeed to produce happiness and internal calmness on mankind. Nevertheless, in other side, the love that has been mobilized consciously or not has become the source of an amount of crime, poverty and backwardness of mankind. As the consequence, credibility of religion and faith to God begins to be questioned. Among the religion critics, secularization are included as the most hated by the religionists. The purpose of secularization that want to place God proportionally in human life and make human as God’s co-Creator or “friend” to create their world has been interpreted differently. Secularization is regarded has been trying to withdraw part of God’s power in human life.